Meningkatkan Kemampuan Menulis Karangan Narasi melalui Pendekatan Kontekstual dengan Inspirator Lingkungan Sekolah Siswa Kelas VIII-1 SMP Negeri 1 Brang Rea - Saerni (Jurnal LENTERA: Jurnal Studi Pendidikan, 2021)
This study aims to find out and reveal that the application of a contextual approach with school environment inspiration can improve the ability to write narrative essays for class VIII-1 students of SMP Negeri 1 Brang Rea, and find out and find contextual learning steps to improve narrative essay writing skills. The subjects of this study were students of class VIII-1 SMP Negeri 1 Brang Rea. This research uses a classroom action research design and was carried out in the 2018/2019 academic year, carried out in three cycles, in which the three cycles discussed one linguistic aspect, namely "writing narrative essays". Following the action research design, activities are carried out in each cycle, including planning, implementing actions, observing actions, and reflecting on actions and their results. The technique used in collecting data is the observation sheet technique and the test technique. The data were processed using qualitative descriptive techniques. Based on the results of data analysis, it turns out that the contextual approach can improve the quality of learning to write narrative essays for class VIII-1 students of SMP Negeri 1 Brang Rea, 2018/2019 academic year. This can be observed from the acquisition of the average score of students who experienced a significant increase. In the initial test results, the average score of students only reached 60. The average score of students increased in the first cycle test to 68, increased to 78 in the second cycle. The contextual approach can provide opportunities for students to compete in compiling narrative essays according to the characteristics of narrative essays. Changes in behavior or attitudes appear in learning to compose narrative essays